Clinical and radiological outcome of anterior inferior plating of middle third fracture of clavicle - Jha, Subash Chandra; Koirala, Shreel; Sah, Shambhu (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Various techniques have been documented for managing fractures of the middle third of the clavicle. This prospective study aimed to assess the outcomes of anterior-inferior plating using a 3.5-mm reconstruction locking plate for middle-third clavicle fractures.Method: Sixty-eight patients presenting with middle-third clavicle fractures underwent treatment via anterior-inferior plating. Surgical indications included complete displacement, severe comminution, and significant shortening of the clavicle (greater than two cm).Result: The mean duration for fracture union was 14 weeks . At the most recent follow-up, all patients had resumed their pre-injury activity levels. No cases required plate removal due to implant-related complications till final follow-up.Conclusion: Anterior-inferior plating is an effective treatment modality for middle-third clavicle fractures, offering stable fixation with minimal complications. This technique mitigates the risk to vital structures beneath the clavicle and is associated with a low incidence of implant prominence issues.